SELF-EFFICACY AND FAMILY RESILIENCE AFFECTS SMARTPHONE ADDICTION IN ADOLESCENTS - Sang Ayu Made; Alfafa Mamnunia , Aghna (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The phenomenon of smartphone addiction among teenagers continues to increase every year. This must be addressed because it can have an impact on teenagers, including academic problems, psychological and physical problems. The research used the Chi Square test with cross sectional approach, the sample was 207 teenagers and sampling was carried out using a stratified simple random sampling was carried out using a stratified simple random sampling technique. Data was obtained using the General Self Efficacy Scale, Walsh Family Resilience Questionnaire, dan Smartphone Addiction Scale Short Version. The research results showed that there was a relationship between self-efficacy and smartphone addiction in teenagers, with a p-value of 0,008 (<0,05) and there was also a relationship between family resilience and smartphone addiction in adolescents, a p-value of 0,041 (<0,05). Teenagers are advised to be more active in participating in positive activities in order to increase self-efficacy, and families can strengthen relationships with teenagers through communication or direct presence so that teenagers do not need to look for happiness from outside by using smarthphone.